ASAS LEGALITAS DALAM HUKUM PIDANA NASIONAL DAN HUKUM PIDANA INTERNASIONAL - Situngkir, Danel Aditia (Soumatera Law Review, 2018)
The principle of legality is the oldest principle of criminal law and is almost found throughout the national criminal law in the world. The existence of this principle is simply to protect citizens from the arbitrariness of the authorities. The strengthening of the issue of human rights contributes to the development of the legality principle, both from national criminal law and international criminal law. Events relating to this issue affect the application of legality principles in law enforcement. The issues to be discussed in this paper are the theoretical principles of legality in criminal law in general and the development of legality principles in national criminal law and international criminal law. The research was conducted by normative juridical method with data collection method through literature study. The application of the principle of legality both in national criminal law and in international criminal law is not rigid, especially to combat crimes against human rights. But in national criminal law must be made in written rules, whereas in international criminal law can be referenced from customary international law.